Penderitaan: Suatu Kajian Teologis Kitab Ayub Dan Relevansinya Terhadap Keluarga Kristen Masa Kini - Berutu, Rosmina; Elisamark Sitopu; Bernard Lubis (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This research is a theological study of Job's suffering. In order to make this suffering relevant to believers, one of the books that attracts attention to be discussed is the book of Job. Job's story is still a topic of conversation to this day when someone faces suffering. Suffering can be experienced by humans, both men and women, both young and old, rich and poor, even children. Every Christian person or family must have faced tragedies in their own lives, for example death, loss of property, illness, economic crisis and ect. Job was a man who was pious, honest, feared God and shunned evil and could experience severe and extreme suffering. The goal is that Christians are motivated to persist in the faith, when suffering is unavoidable. Based on a theological study of the story of Job's suffering, several correct understandings of the emergence of suffering are obtained which are relevant for the lives of Christian families who experience suffering and strengthen Christian families who experience suffering. The Christian family cannot be separated from the reality of suffering and one day the Christian's faith will be tested by God. However, this suffering should make you increasingly know God and glorify Him.